Diabetes; the bidirectional face of COVID-19 - Dr. Saeeda Baig (ziauddin University, 2024)
Although COVID-19 hypothetically, is to cause lethal respiratory disease, yet it led to many metabolic co-morbidities including hyperglycemia. New-onset diabetes was observed as one of the more frequent co-morbidities of COVID-19. The subjects, who had developed hyperglycemia with raised HbA1c, neither had previous diabetes nor had a family history of diabetes, with normal levels of HbA1cAlthough COVID-19 hypothetically, is to cause lethal respiratory disease, yet it led to many metabolic co-morbidities including hyperglycemia. New-onset diabetes was observed as one of the more frequent co-morbidities of COVID-19. The subjects, who had developed hyperglycemia with raised HbA1c, neither had previous diabetes nor had a family history of diabetes, with normal levels of HbA1c